2020
DOI: 10.3233/ch-199233
|View full text |Cite
|
Sign up to set email alerts
|

Pododermal angioarchitecture in the equine hoof wall: A light and scanning electron microscopic study of the wall proper

Abstract: BACKGROUND: Blood supply is an important factor for the normal function of the equine hoof, but earlier studies present conflicting data on functional characteristics of its angioarchitecture. OBJECTIVE: Emphasis was laid on demonstration of the microvascularisation in the different hoof wall regions, aiming at assessment of specialised vascular structures, e.g. vascular sphincter mechanisms and arteriovenous anastomoses. METHODS:The angioarchitecture of the adult pododerma in the equine hoof wall was examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…An area of increased temperature was detected in the area of the frog, consequence of the distal arteries that supply the navicular area [ 6 ] where the blood supply can decrease as a result of thrombosis of the distal arterioles that supply the navicular bone, leading to pain and ischemic necrosis [ 34 ]. Along the hoof wall surface hoof print, the temperature distribution was different, showing areas of increased temperature probably due to the adaptation of blood vessels to the weight-bearing forces transferred to the microvasculature of the pododerma [ 35 ]. No areas of increased temperature were observed in the toe region considering the fact that in non-lame horses the support on the ground is achieved with the entire hoof and in palmar foot pain the support on the ground is sustained by the toe instead of the caudal part of the foot [ 33 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…An area of increased temperature was detected in the area of the frog, consequence of the distal arteries that supply the navicular area [ 6 ] where the blood supply can decrease as a result of thrombosis of the distal arterioles that supply the navicular bone, leading to pain and ischemic necrosis [ 34 ]. Along the hoof wall surface hoof print, the temperature distribution was different, showing areas of increased temperature probably due to the adaptation of blood vessels to the weight-bearing forces transferred to the microvasculature of the pododerma [ 35 ]. No areas of increased temperature were observed in the toe region considering the fact that in non-lame horses the support on the ground is achieved with the entire hoof and in palmar foot pain the support on the ground is sustained by the toe instead of the caudal part of the foot [ 33 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to the results reported in human forensic medicine, where the arterial and venous phases are designed to expand the arterial or venous systems, respectively ( 19 , 34 ). A possible explanation for this disparity is the high number of arteriovenous shunts in the equine limb ( 35 , 36 ) allowing for efficient filling of the venous side during arterial perfusion. Additionally, while the human MPMCTA-protocol suggests longer venous than arterial perfusion ( 19 ), perfusion duration in this study was based on the time needed for contrast material to be observed exiting the limb, which was longer for the first (arterial) phase.…”
Section: Discussionmentioning
confidence: 99%